KUALITAS PELAYANAN PERNIKAHAN DI KABUPATEN TEGAL (The Quality of Marriage Services Offered by KUA in Tegal District) - Lilam Kadarin Nuriyanto (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2016)
The numbers of marriage conducted by the office of ministry of religious affairs in  Tegal District is considered as high in which it is included in the biggest of five in  Central Java province. From January 2016 to June 2016, there are 3.928 marriages that were serviced by the office of ministry of religious affairs in such town. This study aims to explore the quality of services provided by such office whether it is in line with the people’s expectation and its reality or not. This research uses qualitative approach and it is conducted at four offices of ministry of religious affairs (KUA/Kantor Urusan Agama) in four sub districts including Adiwerna, Lebaksiu, Talang and Dukuhturi. Results of this research depict that the index of people’s expectation toward services offered by those offices are 81,30 which is considered as in a good level. However, there still needs some emendation in the management system and enhancement of human resources. This emendation will play to narrow the gap between consumer’s expectation on the offered services and the reality that they are gained.